A new method for non-Fourier thermal response in a single layer skin tissue. (March 2015) - Kundu, Balaram; Dewanjee, Debojit
Abstract: The non-Fourier and Fourier thermal responses in one-dimensional single layer skin tissue under selective boundary conditions are investigated by applying the Laplace Transformation method (LTM). The present method accurately describes the deviation of the temperature response of the non-Fourier model from the Fourier model and roles of important physiological parameters. A systematic exact analytical study on the discrepancies between the thermal wave model and the Pennes' bioheat model shows that the present method is an alternate reliable technique to describe the complicated bioheat problems under different boundary conditions. Three cases, namely constant skin temperature, constant and variable heat flux conditions at the skin surface have been taken to determine the tissue temperature whereas an insulated condition at the core has always been satisfied. From the result, it can be highlighted that cosine heat flux at the skin surface amplifies non-Fourier's response of temperature as well.